Do socially isolated children become socially isolated adults?. (December 2021) - Lay-Yee, Roy; Matthews, Timothy; Moffitt, Terrie; Poulton, Richie; Caspi, Avshalom; Milne, Barry
Highlights: We undertake trajectory analysis of social isolation in a birth cohort. 1/4 of isolated children become isolated adults; 1/3 of isolated adults were isolated children. Child behaviour is associated with isolation in children. Family environment is associated with isolation in children and adults. We find opportunities exist to prevent social isolation and its persistence. Abstract: Social isolation - the lack of social contacts in number and frequency – has been shown to have a negative impact on health and well-being. Using group-based trajectory analysis of longitudinal data from a New Zealand birth cohort, we created a typology of social isolation based on onset during the life course and persistence into adulthood. We then characterized each type according to risk factors related to family environment and child behavior that have been shown previously to be associated with social isolation. Based on fit statistics and distinctness of trajectories we considered the four-class model to be the most appropriate: (1) 'never isolated' (71.6 % of the cohort), (2) 'adult only' (10.1 %), (3) 'child only' (14.3 %), and (4) 'persistent isolation' (4.0 %). Family-environmental factors – i.e. having a teen-aged mother, having a single parent, frequent changes in residence, or maltreatment – tended to be associated with both child and adult onset and persistence of social isolation, whereas child-behavioral factors – i.e. self-control or internalizing symptoms – applied more to the child onset of social isolation. Sensitivity analyses using empirically defined groups – based on 15 % 'cut-offs' for isolation in childhood and adulthood - produced similar life-course groupings and similar associations. Our findings provide insights into the development of social isolation and demonstrate the changeability of social isolation across almost four decades of the life span. They also suggest family-based and child-based interventions could address child onset and the persistence of social isolation into adulthood.